Visitor’s Motivation: A Study of Surajkund Craft Fair of Haryana: Exploring Motivational Indicators of Visitors to Surajkund Craft Fair of Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study aims to examine the visitor’s motivation Surajkund crafts fair Faridabad. This paper adopted primary and secondary data source of data collection. A number of cultural and religious events like fairs and festivals are celebrated in India which attracts a large number of visitor’s. Surajkund International Craft Fair in Haryana to promote handicrafts, handlooms with the help of craftsmen invited at global level. Surajkund Crafts fair has also embodied cultural amalgamation of various countries. In this study the researcher selected 66 respondents to explore the motivational indicator and analyze motivational level of tourists to visit largests craft fair in the world.